Claulansine F suppresses apoptosis induced by sodium nitroprusside in PC12 cells. (July 2013) - Li, J. W.; Ning, N.; Ma, Y. Z.; Zhang, R.; Tan, F.; Chen, N. H.
Abstract Reactive oxygen species (ROS) are known to be involved in many neurodegenerative diseases. This study assessed the effect of Claulansine F, a new carbazole isolated from Clausena lansium, on sodium nitroprusside (SNP)-treated rat pheochromocytoma PC12 cells. First, it was found that Claulansine F showed more potential on inhibiting the programmed death of PC12 cells than edaravone by cell viability, morphologic observation, and flow cytometric analysis. Further results also showed that Claulansine F attenuated the production of total intracellular ROS formation and lipid peroxidation in PC12 cells, inhibited the mitochondrial membrane potential (MMP) loss, and prevented the programmed cell death event via the P53/Bcl-2 family pathway. Its protective effect was likely medicated by the hydroxyl radical (·OH) scavenging ability, as it appeared to be not involved in the natural antioxidant system. These results suggested a promising potential for Claulansine F as a ROS scavenger in pathologies, where an oxidative stress is involved.